Micturition Control with Activation of EUS Nerves at the Spinal Cord Using Fiber Optic Stimulation - Hong, Jinki; Shin, Hyun Joon (Springer Nature, 2026)
This study combines optogenetics and retrograde transfection techniques to functionally target external urethral sphincter (EUS)-related neurons in the spinal cord and to demonstrate a proof-of-concept approach for modulating EUS activation, thereby influencing micturition. Experiments were conducted using C57BL/6 mice, in which an AAV vector (AAV2/6-eSyn-hChR2(H134R)-EGFP) was delivered to the EUS muscle, enabling retrograde transport and subsequent expression of light-sensitive proteins in motor neuron cell bodies within the spinal cord. Electromyography (EMG) of the EUS muscle in response to spinal cord photostimulation was then analyzed using fiber optics, showing that the muscle could maintain electrical activity for up to 60 s during illumination under our stimulation conditions. Finally, the real-time effects of spinal cord photostimulation on micturition were assessed via cystometry. When the bladder was sufficiently filled, 60 s of spinal cord stimulation extended continence time in proportion to the stimulation period (from 45 ± 8 s to 101 ± 14 s). These findings demonstrate that retrograde transfection from peripheral muscle to spinal motor neurons enables expression of light-sensitive proteins and allows optogenetic activation of neurons associated with the EUS. Moreover, fiber-optic stimulation effectively modulated EUS activity and micturition in situ. This electroceutical approach provides a proof-of-concept framework that may inform future strategies for treating urinary disorders and for investigating neural circuit function.